Feiras de ciências como oportunidades de (re) construção do conhecimento pela pesquisa - FARIAS, Luciana de Nazaré (2006)
At the present work, I report a qualitative research on a narrative model, in which I intended to investigate in what level does Science Fair contribute to teachers and students formation and development and to which level does Science Fair represent opportunities for community socialization and interaction. With this purpose, I analyze semi-structured interviews that I have developed with ten teachers and six students, participants of the XI FEICIPA Science Fair of Pará State, which have occurred at Abaetetuba, PA, in December, 2003. Field diaries and documents referred to Science Fair realized at Pará State have also become objects of analyses. By research subjects reports, I have noted different opportunities of formation generated by their lived/shared experiences during Science Fair. I believe that Science Fair can contribute to the socialization and exchange of teaching/learning/knowledge within the community, generating an enlargement of the Science Fair participants, expositors and visitors world vision, allowing the research results spread and experience exchange between pairs, as a means to validate knowledge. I conclude by putting in evidence some emerged iterative categories of investigated persons speech, related to teaching as/to research and Science Fair: it develops enquiry curiosity; privileges the option for significant social contents; contributes to constant asking preparation; generates (re)building and socialization of knowledge; allows the resolution of real problems in/of the community; demands to make decisions; generates professional development; develops the ability to learn to learn and promotes (trans)formation of people.